The abundance of Malaysian giant ant in urban forest patches in relation to microclimate - Johari, Muhammad Farhanjafni (2018)
In Malaysia, forest fragmentation has become a great concern which resulted environmental degradation. Forest fragmentation occurs when original large and continuous forest is divided into small forest patches. Forest fragmentation gives an effect to the forest fauna diversity such as the Malaysian Giant Ant. Therefore, this study was conducted to investigate the abundance of the Malaysian Giant Ant within four fragmented forests in Selangor. Located within urban landscape the four fragmented forest reserves were Sungai Lalang Forest Reserve (SLFR), Ayer Hitam Forest Reserve (AHFR), Bukit Cerakah Forest Reserve (BCFR) and Bangi Forest Reserve (BFR). Point transect survey was used with thirty sampling points at all sites. AHFR was recorded the highest abundance of Malaysian Giant Ant compared to other sites. This result is somewhat contradictory with previous studies that suggested large sized forest had a high abundance of species. The findings may due to other factors that affected more the abundance of Malaysian Giant Ant such as food resources, number of predator and rate of disturbance at the sites. For habitat quality, abundance of the Malaysian Giant Ant was affected by relative humidity, canopy cover and the number of palms. Therefore from these results, increase in the abundance of Malaysian Giant Ant can assist in conserving the biodiversity and balancing the ecosystem since this species plays important roles in the urban forest ecosystem.